Czynniki przetrwania na zesłaniu - na przykładzie matek Sybiraczek = Factors for survival in exile - case of mothers deported to Siberia - Bazuń, Dorota (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The text concerns the forced deportation of Polish women and their families into the USSR during the Second World War. Strategies of surviving the traumatic situation of exile were the subject of the analysis. It was attempted to determine the role of diverse resources: material, social, cultural and symbolic ones during exile.
Keywords: deportacje przymusowe; trauma; II (druga) wojna światowa; kobiety; kapitały; forced deportations; world war II; women; capitals